First record of melanism in Phyllotis limatus (Rodentia: Cricetidae): with an update list of melanic wild mammals of the World - Medina Valdivia, Yasmy Karina (2019)
Here, we report the first case of melanism in the rodent Phyllotis limatus, which increase the number of wild mammal species with melanism to 113 species, worldwide. The orders Rodentia and Carnivora group the largest number of species with melanism, being reported more frequently in countries of America, followed by Asia, Africa, Europe and Oceania. In South America, Brazil is the country with the highest number of species with melanism, with eight species, followed by Peru with five. The melanic checklist of wild mammals presented here suggests that blackish coloration is relatively frequent mutations in some species, therefore, we hope the register numbers of species with melanism will be increased in future investigations.